Development of Trawls for Medium Sized Trawlers for Veraval, North east coast of India - KUNJIPALU, K K; MATHAI, P GEORGE; KUTTAPPAN, A C (Fishery Technology, 2017)
Comparative fishing experiments with 25 m bulged belly and 25 m six seam trawls were carried out to study the relative efficiency of the gear. Bulged belly trawl was found more efficient than the other at depths below 40 m. The tension and horizontal opening were more in bulged belly and six seam trawl respectively. Bulged belly caught more of prawns and lobsters but there was no significant difference in the catch of sciaenids, cephalopods and ribbon fishes in the two nets.